Non-adherence in difficult asthma: time to take it seriously. Issue 3 (18th June 2011) - Heaney, Liam G; Horne, Rob
Abstract : Recent studies have demonstrated a high prevalence of non-adherence with anti-inflammatory medication in patients referred for specialist assessment with difficult-to-control asthma. As well as poor asthma outcome and increased healthcare cost, failure to detect non-adherence makes identification of true treatment-resistant/refractory asthma challenging. This is because guideline definitions of refractory asthma are all predicated on failure to respond to high-dose anti-inflammatory therapy but do not state how adherence with this therapy should be assessed. With the advent of novel expensive biological therapies, the systematic identification of non-adherence becomes more essential to avoid targeting therapies at an inappropriate patient group. Novel biomarkers of steroid exposure, in combination with more traditional surrogate measures such as prescription filling assessment, may allow more objective assessments of non-adherence to be developed in the future. When identified, non-adherence can potentially be targeted and improved, but the key challenge is to empower patients to make informed choices about medicines rather than decisions influenced by misplaced beliefs about benefit and harm. There is an urgent need for the systematic development of individualised interventions which allow non-adherence to be effectively managed. Thus, non-adherence must become a priority in the clinical assessment of difficult-to-control asthma because addressing non-adherence is likely to deliver greater benefits in this group than any novel treatment. It is essential that future research examines strategies and interventions to address non-adherence in subjects with difficult-to-control asthma.